2015
DOI: 10.3109/00207454.2015.1054481
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic neuromyelitis optica spectrum disorders: three new cases and a review of the literature

Abstract: Neuromyelitis optica spectrum disorders (NMOSD) occasionally develop in patients with tumor in relation to aquaporin-4 IgG (AQP4-IgG), representing a new paraneoplastic phenomenon. We reported three patients with paraneoplastic NMOSD and provided a comprehensive review of the literature. A total of 34 cases with paraneoplastic NMOSD were identified from our own case database (n = 3) and the previous literature (n = 31). The median age at NMOSD-related symptom onset was 50.5 years, and 91% of the cases were fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…As for the breast carcinoma found in NMOSD, there was an observation about 41 patients with positive NMO-IgG, six malignancies were identified in five NMOSD seropositive patients, inluding breast carcinoma (three cases), lymphoma, cervical carcinoma and leiomyosarcoma (in a patient who also had breast carcinoma) [12]. Furthermore, from another studies of 34 paraneoplastic NMOSD cases, 11 (32%) cases had breast carcinoma [13]. We should attach importance to the detection of paraneoplastic etiology, especially the breast carcinoma in NMOSD cases.…”
Section: Case Presentationmentioning
confidence: 96%
“…As for the breast carcinoma found in NMOSD, there was an observation about 41 patients with positive NMO-IgG, six malignancies were identified in five NMOSD seropositive patients, inluding breast carcinoma (three cases), lymphoma, cervical carcinoma and leiomyosarcoma (in a patient who also had breast carcinoma) [12]. Furthermore, from another studies of 34 paraneoplastic NMOSD cases, 11 (32%) cases had breast carcinoma [13]. We should attach importance to the detection of paraneoplastic etiology, especially the breast carcinoma in NMOSD cases.…”
Section: Case Presentationmentioning
confidence: 96%
“…Dutra et al [15] as well as Annus et al [16] stated that late onset of NMOSD after the age of 50 should raise the suspicion of paraneoplastic disorders. This assumption was reinforced by the work of Cai et al [11] who found that half of patients with paraneoplastic NMOSD were over 50 years, compared with only 16% of patients with non-paraneoplastic NMO. In other words, NMOSD, is more likely to be paraneoplastic in patients aged over 50 years at the onset of symptoms.…”
Section: Neuromyelitis Optica As a Paraneoplastic Manifestation Of Brmentioning
confidence: 97%
“…Interestingly, paraneoplastic NMOSD has been associated with collapsing response-mediator protein 5 (CRMP5/anti-CV2) antibodies and amphiphysin antibodies in patients with small cell lung carcinoma, thymoma and renal cancer [11].…”
Section: Neuromyelitis Optica As a Paraneoplastic Manifestation Of Brmentioning
confidence: 99%
“…Spinal cord sarcoidosis may sometimes mimic NMO TM but there are other suggestive features and AQP4 is not positive 5. NMOSD may be paraneoplastic and precede tumour detection in almost half of these rare cases (especially breast cancer) 6. However, autoimmunity is its most important association 7.…”
Section: Differential Diagnosismentioning
confidence: 99%